Efficacy of radical cystectomy plus adjuvant intraarterial chemotherapy with gemcitabine and cisplatin on locally advanced bladder cancer - Jiang, Lijuan; Zhang, Zhiling; Dong, Pei; Li, Yonghong; Yao, Kai; Liu, Zhuowei; Han, Hui; Qin, Zike; Yao, Min; Zhou, Fangjian (Chinese medical journal, 2014)
Background Bladder cancer is the ninth most common cancer in the world; fewer than 15％ of transitional-cell carcinoma patients survive 2 years if left untreated.Although radical cystectomy is the standard treatment of choice,much of them relapse and the necessity of adjuvant chemotherapy is still under debate.The aim of the study was to evaluate the efficacy of adjuvant intraarterial chemotherapy （IAC） with gemcitabine and cisplatin （GC） on locally advanced bladder cancer.Methods This is a retrospective study on 60 patients with locally advanced bladder carcinoma who underwent radical cystectomy between May 2000 and June 2011.Patients were studied in two groups based on IAC and followed up for up to 5 years.Results Among 60 patients,there were 25 patients who underwent IAC （GC） after radical cystectomy （the IAC group） and 35 patients who underwent radical cystectomy alone （the control group）.Although not significant,the relapse rates were slightly reduced in the IAC group than in the control group.Patients with IAC had a reduction in mortality compared with patients without IAC over 5 years.Specifically,IAC significantly reduced about 82％ of mortality within the first year （hazard ratio=0.18,95％ Cl 0.03-0.97,P=-0.04）.Additionally,IAC was well tolerated and safe.The most common adverse effect was transient myelosuppression （10/25,40％）,which was resolved by various medical treatments.Conclusions Compared with radical cystectomy alone,radical cystectomy in combination with adjuvant IAC moderately but significantly reduces 1-year mortality.Our preliminary data showed only marginal benefit for the early survival.However,a randomized clinical study is needed to determine the long-term survival benefit.